The Influence of KCP (Knee Chest Position) Gymnastics on Decreasing Fetal Head - Yeni Nurhayati; Ninik Indayani (Proceedings of the International Conference on Nursing and Health Sciences, 2023)
The lowering of the bottom part of the fetus is very important in assessing the progress of labor. Even so, it cannot be certain that the fetus enters the upper door of the pelvis (PAP) on time. In pregnancy where the fetal head is slow to enter the PAP, it is very likely that there will be long partus, overdue pregnancy and breech conditions or buttocks presentation that can harm the mother and fetus. One effort to try to reduce the fetal head is the knee-chest position or chest-knee position. The purpose of this study was to analyze the effectiveness of knee chest position (KCP) gymnastics against the lowering of the fetal head to enter the upper door of the pelvis (PAP). This research is an experimental quasy. In this study, the sample was divided into 2 groups, namely intervention as many as 15 people and control group 15 people. The sampling technique is purposive sampling Bivariate analysis used in this study is to determine whether there is a relationship between the two groups, namely with the independent t test. Based on the results of the independent t test, it was found that there was an effect of knee chest gymnastics on the decrease in fetal head to enter PAP and was statistically significant because the p value was 0.020 < 0.05.